Mirach’s goblin: discovery of a dwarf spheroidal galaxy behind the Andromeda galaxy - Martínez-Delgado, David; Grebel, Eva K. (Astronomy and astrophysics, 2018)
It is of broad interest for galaxy formation theory to carry out a full inventory of the numbers and properties of dwarf galaxies, both satellite and isolated, in the Local Volume.Aims. Ultra-deep imaging in wide areas of the sky with small amateur telescopes can help to complete the census of these hitherto unknown low-surface-brightness galaxies, which cannot be detected by the current resolved stellar population and HI surveys. We report the discovery of Donatiello I, a dwarf spheroidal galaxy located one degree from the star Mirach (β And) in a deep image taken with an amateur telescope.Methods. The color-magnitude diagram (CMD) obtained from follow-up observations obtained with the Gran Telescopio Canarias (La Palma, Spain) reveals that this system is beyond the local group and is mainly composed of old stars. The absence of young stars and HI emission in the ALFALFA survey is typical of quenched dwarf galaxies. Our photometry suggests a distance modulus for this galaxy of (m − M) = 27.6 ± 0.2 (3.3 Mpc), although this distance cannot yet be established securely owing to the crowding effects in our CMD. At this distance, the absolute magnitude (MV = −8.3), surface brightness (μV = 26.5 mag arcsec−2), and stellar content of Donatiello I are similar to the “classical” Milky Way companions Draco or Ursa Minor.Results. The projected position and distance of Donatiello I are consistent with this object being a dwarf satellite of the closest S0-type galaxy NGC 404 (“Mirach’s Ghost”). Alternatively, it could be one of the most isolated quenched dwarf galaxies reported so far behind the Andromeda galaxy.